Aerobic-Anoxic Filter For Nitrogen Removal From Domestic Wastewater: A Comparison Study - Hamdan, Rafidah; Nur Amira Atierah Mohammed Shaikhani; Nur Ain Nazirah Mohd Arshad (Recent Trends in Civil Engineering and Built Environment, 2020)
Treatment plant discharges from the domestic wastewater are among the major environmental sources of nitrogen pollution. However, the removal of nitrogen from wastewater often requires high cost of chemical treatment technology, to prevent the overloading of nutrients into the surface water body. Therefore, the laboratory scale of the Semi Aerated L-shape Steel Slag Filter was supposed to be designed to remove total nitrogen from domestic wastewater. The Semi Aerated L-shape Rock Filter system is a combination of vertical aerated rock filter and horizontal rock filter (VARF & HRF) with steel slag used as filter media. The main objective was to study the effectiveness of nitrogen removal from domestic wastewater by using Semi Aerated L-shape Steel Slag Filter system in aerobic-anoxic condition. The influent and effluent sample of the filter were supposed to be collected and analyzed for Total Nitrogen, Chemical Oxygen Demand, Dissolved Oxygen, Ammoniacal Nitrogen, and pH to monitor the effectiveness of the filter. Due to the outbreak of COVID-19, the laboratory result was replaced by comparing the result from the previous study. Results obtained from a previous study show that the efficiency of an aerobic-anoxic system in removing COD, TN, ammonia, and nitrate can almost reach to 100%.